The Long-Run Growth Effects of R&D Subsidies - Paul S. Segerstrom (The Research Institute of Industrial Economics (IUI), 1998)
This paper presents a model of R&D-driven growth without scale effects where firms can engage in both horizontal and vertical R&D activities. Unlike in earlier models of R&D-driven growth without scale effects by Jones (1995), Segerstrom (1998) and Young (1998), R&D subsidies can have long-run growth effects. Indeed, for a wide range of parameter values, a permanent increase in the R&D subsidy rate decreases the long-run rate of economic growth. An intuitive explanation for why R&D subsidies sometimes retard growth and sometimes promote growth is provided.
Keywords: O32; O41; 330; Economic growth; R&D; Forschungssubvention; Wirtschaftswachstum; Theorie